Satu ANALISIS FAKTOR HARGA INTERNASIONAL GANDUM, PENGGUNAAN GANDUM, PDB, DAN JUMLAH PENDUDUK INDONESIA TERHADAP IMPOR GANDUM HS (1001) DI INDONESIA TAHUN (2000-2022): Impor Gandum Indonesia - Alfiansyah, Arif Alfiansyah; MArseto, Marseto (Universitas Pasundan, 2025)
Indonesia needs to meet the food needs of its citizens because its population continues to increase. Because it is difficult to produce, Indonesia imports a lot of wheat to meet consumption needs. This research aims to: 1) Examine the factors that influence the volume of Indonesian wheat imports, 2) Analyze the influence of world international wheat prices, wheat use, GDP and Indonesian population on Indonesian wheat imports. This research uses secondary data sourced from the Directorate General of Agriculture, Central Statistics Agency (BPS), and the World Bank in the form of world international wheat prices, wheat use, GDP and Indonesia's population for the last 23 years (2000-2022). SPSS 25 was used to process the data. This research uses quantitative methods with multiple linear regression analysis which uses classical assumption tests and hypothesis testing. The results of the research show that international wheat prices have a negative and not significant influence on the volume of Indonesian wheat imports, the use of wheat has a positive and significant influence on the volume of Indonesian wheat imports, Indonesian GDP has a negative and insignificant influence on the volume of Indonesian wheat imports. And the population of Indonesia has a positive and insignificant influence. Keywords: Wheat Import, HGI, use of wheat, GDP, Population